Corruption schemes while purchasing medicinal products at the expense of state funds in Ukraine - Аркуша, Лариса Ігорівна; Аркуша, Л. І.; Аркуша, Лариса Игоревна; Arkusha, Larysa I.; Загородній, Віктор Євстафійович; Загородній, В. Є.; Загородний, Виктор Евстафьевич; Zahorodnii, Viktor Ye.; Zagorodniy, Viktor; Федчун, Наталія Олександрівна; Федчун, Н. О.; Федчун, Наталия Александровна; et al. (Advanced Scientific Research, 2020)
As we know, corruption is recognized as the most widespread abuse in the world, which accompanies purchases in various spheres of society’s life. Thus, corruption in procurement was manifested in 69% of cases in more than 2,400 fraudulent cases detected in organizations across all continents. Since 2015 Ukraine is trying to reform the most corrupt system of public procurement – healthcare sector. According to the Deputy Minister of Health on European Integration O. Stefanishina, up to 40% of the funds were overexpended on the purchase of medicines, vaccines and medicinal products. According to the Law of Ukraine “On Public Procurement”, the Ministry of Health of Ukraine (hereinafter – the MH of Ukraine), with the aim of improving the quality of procurement procedures, ensuring economy of budget funds and satisfying the needs of customers in the field of health care by medicinal products and medicines, has approved the Concept of the Reform of the Mechanisms of Public Procurement of Medicinal Products and Medicines (hereinafter – the Concept) by the order of the Cabinet of Ministers of Ukraine dated from August 23, 2017, No. 582-r. In accordance with the Concept, the Centralized Procurement Organization (hereinafter – the CPO) was established, whose functions in 2019 were assigned to the State Enterprise “Medical Procurement of Ukraine”. Besides, in order to overcome corruption in the field of public procurement of medicines and medicinal products, the MH of Ukraine has been procuring medicines for the fifth consecutive year through international organizations (UNDP, UNICEF Children’s Fund and Crown Agents UK procurement agency), which saved up to 40% of budget funds.

Як ми знаємо, корупція визнана найпоширенішим у світі зловживанням, яке супроводжує закупівлі в різних сферах життя суспільства. Таким чином, корупція у сфері закупівель виявилась у 69% випадків у понад 2400 випадках шахрайства, виявлених в організаціях на всіх континентах. З 2015 року Україна намагається реформувати найбільш корумповану систему державних закупівель - сектор охорони здоров'я. За словами заступника міністра охорони здоров’я з питань європейської інтеграції О. Стефанішиної, до 40% коштів було перевитрачено на придбання ліків, вакцин та лікарських засобів. Відповідно до Закону України “Про публічні закупівлі”, Міністерство охорони здоров’я України (далі - МОЗ України), з метою підвищення якості процедур закупівель, забезпечення економії бюджетних коштів та задоволення потреб споживачів у галузі охорони здоров’я лікарськими засобами та ліками, затвердив Концепцію реформи механізмів державних закупівель лікарських засобів та ліків (далі - Концепція) розпорядженням Кабінету Міністрів України від 23 серпня 2017, No 582-р. Відповідно до Концепції була створена Централізована організація закупівель (далі - ЦЗО), функції якої у 2019 році були покладені на Державне підприємство «Медичні закупівлі України». Крім того, для подолання корупції у сфері державних закупівель ліків та лікарських засобів МОЗ України вже п’ятий рік поспіль закуповує ліки через міжнародні організації (ПРООН, Дитячий фонд ЮНІСЕФ та агентство закупівель Crown Agents UK), які заощадили до 40% бюджетних коштів.

Как мы знаем, коррупция признана самым распространенным в мире злоупотреблением, которое сопровождает закупки в различных сферах жизни общества. Таким образом, коррупция в сфере закупок оказалась в 69% случаев в более 2400 случаях мошенничества, выявленных в организациях на всех континентах. С 2015 года Украина пытается реформировать наиболее коррумпированную систему государственных закупок - сектор здравоохранения. По словам заместителя министра здравоохранения по вопросам европейской интеграции А. Стефанишиной, до 40% средств было перерасходовано на приобретение лекарств, вакцин и лекарственных средств. В соответствии с Законом Украины "О публичных закупках", Министерство здравоохранения Украины (далее - МЗ Украины), с целью повышения качества процедур закупок, обеспечения экономии бюджетных средств и удовлетворения потребностей потребителей в области здравоохранения лекарственными средствами и лекарствами, утвердил концепцию реформы механизмов государственных закупок лекарственных средств и лекарств (далее - Концепция) распоряжением Кабинета Министров Украины от 23 августа 2017, No 582-р. Согласно Концепции была создана Централизованная организация закупок (далее - ЦЗО), функции которой в 2019 году были возложены на Государственное предприятие «Медицинские закупки Украины». Кроме того, для преодоления коррупции в сфере государственных закупок лекарств и лекарственных средств МЗ Украины уже пятый год подряд закупает лекарства через международные организации (ПРООН, Детский фонд ЮНИСЕФ и агентство закупок Crown Agents UK), которые сэкономили до 40% бюджетных средств.
Arkusha L. Corruption schemes while purchasing medicinal products at the expense of state funds in Ukraine / L. Arkusha, V. Zagorodniy, N. Fedchun // International Journal of Pharmaceutical Research. - V. 12 (3). – Advanced Scientific Research, 2020. – P. 1465-1470.